Modulatory effects of Micromeria Barbata and 3-acеtyl-11-kеto-boswеllic acid on advanced glycation end products-induced inflammatory cytokine response in THP-1 cells - Saad, May; El-Achkar, Ghewa A; Hajj, Rana El; Rahman, Abir Abdel; Khalil, Mahmoud I.; Nasreddine, Nadine (Edelweiss Applied Science and Technology, 2025)
Advanced glycation end products (AGEs) contribute to diabetes complications. They activate inflammation by binding to Receptors for Advanced Glycation End Products (RAGE) on immune cells, triggering cytokine release. Micromeria barbata (MB), a medicinal herb with various biological actions, has not been examined for its anti-inflammatory effects on AGE. Boswellia serrata (BS) research on diabetes and AGE-related conditions is limited. This study examines the anti-inflammatory effects of 3-acetyl-11-keto-boswellic acid (AKBA), BS’s main active component, and MB plant extract on AGE-stimulated THP-1 human monocytic cells. We investigated the impact of AGEs on pro-inflammatory cytokines and the effects of MB plant extract and AKBA on the gene expression of Interleukin-1β (IL-1β), Interleukin-6 (IL-6), Tumor Necrosis Factor-α (TNF-α), Interleukin-10 (IL-10), and Interleukin-4 (IL-4) in AGE-stimulated THP-1 cells. THP-1 cells were unaffected by MB, AKBA, and AGE-BSA at various doses. MB and AKBA may reduce AGE-stimulated THP-1 cell inflammation. Treatment with MB and AKBA significantly decreases IL-6 and TNF-α expression. AKBA (0.027 μg/mL) reduces IL-1β gene expression, while MB has no effect. Furthermore, at higher doses, both MB and AKBA significantly increase IL-10 and IL-4 gene expression. This is the first research to reveal MB and AKBA’s anti-inflammatory effectiveness, shedding light on natural therapeutic agent development.